Efficient catalytic transfer hydrogenation of furfural to furfuryl alcohol over Zr-doped ordered mesoporous carbon synthesized by Zr-arbutin coordinated self-assembly. (1st January 2023) - Xu, Yingying; Liu, Xiaoning; Guo, Haixin; Qiu, Mo; Qi, Xinhua
Graphic abstract: Highlights: Zr-coordinated OMCs with arbutin as the carbon precursor were synthesized. Synthesized Zr@OMCs showed perfectly ordered mesoporous structure. Zr@OMC was efficient for catalytic transfer hydrogenation of furfural to furfuryl alcohol. A high furfural conversion of 100% and furfuryl alcohol yield of 93.2% were achieved. Zr@OMC showed good stability in at least 5 cycles after regeneration. Abstract: The green synthesis of ordered mesoporous carbons (OMCs) with sustainable biomass resources as carbon precursors has attracted widespread interest in various applications. In this work, Zr-doped ordered mesoporous carbon (Zr@OMC) with an environmentally friendly process was synthesized with arbutin (a kind of polyphenol extracted from plants) as the carbon precursor, F127 as the soft template, and Zr 4+ as the cross-linker through the solvent evaporation-induced self-assembly method. The obtained Zr@OMC exhibited highly ordered mesoporous structures with a BET surface area of 375–427 m 2 /g and an average pore size of 3.9–4.6 nm, which exhibited excellent catalytic performance for the conversion of furfural (FF) to furfuryl alcohol (FA) through Meerwein-Ponnodorf-Verley (MPV) reaction with isopropanol as hydrogen donor, and a maximum FA yield of 93.2 % with FF conversion of 100 % could be achieved at 180 °C. Meanwhile, Zr@OMCs could be easily regenerated by heating at 400 °C for 2 h under nitrogen flux to recover its high catalytic activity in FF conversion.